Enzyme focused process engineering: evaluating the influence of complex process environments on enzyme activity - Still, Kristoffer (2018)
Complex process environments such as the treatment of wastewater are susceptible to a high amount of variability. Industrial processes that incorporate a biological component, either microorganisms or enzymes, are especially prone to this variability from multiple external influences. Other examples apart from wastewater treatment include the production of biologically derived chemicals and biopharmaceuticals. Wastewater is highly dynamic as both its characteristics and composition vary over time substantially increasing the level of complexity. Therefore understanding the variability associated with wastewater treatment through enzyme activity provides a foundation for studying the other mentioned biotechnology processes. Enzymes are critical in the treatment of wastewater as they are responsible for remediating the majority of organic pollutants. The incoming wastewater feedstock is converted to a final product that is safe for release into the receiving environment. The main aim of this research was to demonstrate enzyme variability, and identify the environmental and process factors that contribute to this for enzymes both exogenous and inherent to the wastewater system. Exogenous enzymes proposed as endocrine disrupting compound (EDC) treatment technologies and enzymes inherent to the wastewater system were studied. Laccase and tyrosinase were the chosen exogenous enzymes and their ability to remove EDCs investigated. Estrone (E1) was the EDC primarily studied with diclofenac (DCF) included later to analyse the influence mixed substrate solutions have on enzyme performance. E1 and DCF are both on the European Union Watch List due to their adverse effects on aquatic wildlife. An enzymatic water quality parameter was developed to study the temporal variability of E1 removal by laccase and tyrosinase. Previous literature had mostly shown laccase to degrade EDCs in wastewater from a single sample snapshot. The experimental conditions for the developed enzymatic parameter remained constant with the tested effluent varying between sample days. The enzymatic parameter with laccase and tyrosinase was performed over a sampling period of four months. E1 removal (%) was variable for the two enzymes as E1 removal ranged between 54% and 92%. There was little correlation between laccase and tyrosinase performance over this sampling period, even though the two enzymes are oxidoreductases. Average E1 removal (%) for laccase during this sampling period was 74.8% (± 9.6%) and for tyrosinase the average was 83.0% (±. 8.3%). This variability in removal was due to the dynamic nature of the related process and environmental factors such as pH and dissolved oxygen. Constituents in the wastewater can also inhibit laccase and tyrosinase activity. In this research chloride (Cl-) and copper (Cu2+) were the studied inhibitors. DCF was also used to analyse EDC mixture effects with E1. The inhibitory effects were examined in a wastewater matrix unlike the literature that has mainly investigated clean buffer solutions. The addition of Cu2+ at 0.05 mg/L to the enzymatic water quality parameters greatly inhibited tyrosinase performance reducing E1 removal. Compared to the control that contained no added Cu2+ E1 removal was 20% lower. Laccase unlike tyrosinase was also able to remove DCF and the addition of E1 increased DCF removal between 11% and 27% in the effluent, depending on DCF concentration. Inherent enzymes in particular hydrolases are essential in the breakdown of the majority of organic pollutants and the subsequent assimilation by microorganisms within the WWTP activated sludge. Five inherent hydrolases were analysed in this research and they were α-glucosidase, β-glucosidase, alkaline phosphatase, esterase and sulfatase. The activities for these enzymes in the literature had shown to vary considerably between WWTPs and the same WWTP. This understanding was expanded on by measuring inherent activity across a WWTP and correlating the recorded activities with measured standard water quality parameters using Pearson’s correlation. The WWTP sampled from was unique in the UK as it incorporated a membrane bioreactor (MBR) system. Not previously discussed in the literature has been inherent activity associated with returned activated sludge (RAS). The MBR system unlike conventional WWTPs is far more efficient at recycling RAS and retaining enzymes in the system. Inherent activity was reported to be higher in the RAS than the mixed liquor for all hydrolases apart from esterase even when activity was corrected against solid concentration. This shows other influences apart from biomass concentration influencing enzyme activity. The reduction in esterase activity between the RAS and the mixed liquor ranged between 4.7% and 22.1%. Analysing inherent activity throughout the WWTP demonstrated temporal and spatial variability with the contributory environmental and process factors highlighted.